FATTY ACIDS COMPOSITION IN MACADAMIA SEDES OIL (MACADAMIA INTEGRIFOLIA) FROM ECUADOR - CARRILLO W; CARPIO C; MORALES D; VILCACUNDO E; ÁLVAREZ M (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The aim of this study was to determine the fatty acids composition in a macadamia seeds oil sample cultivated in Ecuador. Materials & Methods: macadamia oil was obtained of macadamia seeds using the cold pressing method. Fatty acids analysis was carried out using the Gas Chromathography method with a Mass Selective Detector (GC/MSD) and using the data base Library NIST14.L to identify the compounds. Results: macadamia seeds have a high content of unsaturated fatty acids with 41.36% of oleic acid. Macadamia seeds oil has 37.77% of polyunsaturated fatty acids of which 3.79% É·6 Î±- Linoleic and 33.98% of É·3 Î±- Linolenic. Macadamia seeds only have 9.33% of palmitic acid.Â Conclusions: Macadamia seeds are a good source of monounsaturated fatty acids oleic acid and with a good content of É·6 Î±- Linoleic and É·3 Î±- Linolenic. This profile enables their use as a good and healthy oil to be used in the food industry in Ecuador.Â Keywords: Macadamia, Macadamia integrifolia, Fatty acids, Gas chromatography-mass selective detector, Methyl ester, Omega acids.